Is Strategic Purchasing in Iranian Insurance Companies Effective? - Hoda Faraji; Abbas Kebriaeezadeh (Tehran University of Medical Sciences, 2021)
Since up to 60 percent of health care expenditures in developing countries are allocated to pharmaceutical products, utilizing this budget in order to supply pharmaceutical products is important. Good Procurement Practice (GPP) with the assistance of various ways of tendering is one of the most cost-effective methods in this matter. Studies showed that adding one extra supplier to tendering will cause 10 percent price reduction on average which is considered the most important outcome of tendering. In cases where there are many suppliers, tendering is recommended as a strong method in pricing and reimbursement.   It seemed that GPP in reimbursement companies is not sufficient in Iran. Although bidding in countries that have developed in the generic markets is more common than those that are reaching this goal, it is recommended that reimbursement companies use bidding for inpatients, outpatients, specific patients and product groups, vaccines, and bulk products in cumulative and regional and national level. These would result in optimum use of the public budget.